Deep learning for blockchain in medical supply chain risk management. (15th May 2023) - Jiang, Fei; Jiang, Chen-Xian; Li, Jian Xin
The COVID-19 pandemic's severe shortage of essential medical supplies created significant risks in the medical supply chain operation. Supply chain managers have started focusing on decision-making based on multiple data sources to correctly foresee uncertainty and develop a proactive and predictable intelligent risk management system. These features make using blockchain and Deep Learning (DL) methods in Supply Chain Risk Management (SCRM) feasible but are still in the initial stages. This work provides a comprehensive and detailed literature analysis and emphasises that many blockchains and DL methods are used in various stages of medical SCRM. At the same time, by deploying blockchain and DL and combining them with necessary questionnaires, an effective SCRM model can be used to detect major supply chain risks. By outlining the unresolved challenges that must be solved before the large-scale deployment of DL and blockchain applications. Ultimately, research points out the key direction of future research in this field and promotes global supply chain cooperation.